2021
DOI: 10.3390/cancers13030403
|View full text |Cite
|
Sign up to set email alerts
|

Changing Incidence and Survival of Primary Central Nervous System Lymphoma in Australia: A 33-Year National Population-Based Study

Abstract: Primary central nervous system lymphoma (PCNSL) is a rare brain cancer that remains challenging to study. Epidemiology of PCNSL in the Australian population, which is racially and ethnically diverse, has not been examined previously. Using ICD-O-3.1 Morphology and Topography Codes to identify cases, we analyzed complete datasets from the comprehensive Australian Cancer Database (1982–2014, adults aged ≥ 20 years) to establish incidence rates and trends of PCNSL, and to define survival outcomes of individuals d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…The mean age at diagnosis was 63.1 ± 14.9 years, and the male to female ratio was 1.1:1.0, which was largely consistent with a population-based study from Australia (14). Previous studies have demonstrated that age was a significant and adverse prognostic factor (15)(16)(17).…”
Section: Discussionsupporting
confidence: 86%
“…The mean age at diagnosis was 63.1 ± 14.9 years, and the male to female ratio was 1.1:1.0, which was largely consistent with a population-based study from Australia (14). Previous studies have demonstrated that age was a significant and adverse prognostic factor (15)(16)(17).…”
Section: Discussionsupporting
confidence: 86%
“…17 Its incidence has been steadily increasing during the last two decades. 18 , 19 The treatment of PCNSL has evolved over the years from radiation alone to multi-agent chemotherapy. 20 , 21 With concerns over the long-term neurotoxicity of radiation, 22 oncologists have moved away from WBRT as consolidation in first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse large B‐cell lymphoma is classified as an aggressive lymphoma exhibiting a broad variation in pathobiological and clinical findings defined by the primary site of the lymphoma 6‐9 . The disease behavior in extranodal DLBCLs has been linked to mutational patterns possibly acquired through somatic hypermutation.…”
Section: Introductionmentioning
confidence: 99%